Antecedents to the effectiveness of game-based learning environments for the Net generation: A game task fit and flow perspective - Mosiane, Segomotso (Department of Information Systems, 2017)
Purpose: There is a general consensus that games are effective as learning tools. There is however, a lack of knowledge regarding what makes games effective as a learning tool. The purpose of this study is therefore to answer the question: what are the antecedents of an effective game-based learning environment for the Net generation? The Net generation comprises individuals who prefer to learn using games as a tool. Aim: The aim of this dissertation is to develop a conceptual framework that reflects the antecedents of an effective game-based learning environment for the Net generation. The conceptual framework combines the IS Success Model, and the Task-Technology Fit and Flow theory. Method: The study used a quantitative method. Data was collected using an online instrument. The study used 125 participants from mainly the United Kingdom, United States and South Africa. The model was validated using confirmatory factor analysis and tested using multiple regression analysis. Key Findings: The identified antecedents of effectiveness are Game-Task Fit and Flow, where Flow consists of Clear Goals, Feedback and Concentration. Additionally, the Use factor in the model is replaced by Perceived Usefulness. The Conceptual Framework can be used as an evaluation tool for effective game-based learning environments for the Net generation.